The contribution of physical education and sports attitudes to emotional intelligence: an examination of secondary school students - Murat Sarikabak; Mert Ayrancı; Ebru Ayranci (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The primary aim of this study was to examine the attitudes of secondary school students towards physical education and sports and their emotional intelligence levels. The study was conducted with 360 students. Data were collected using a personal information form and a voluntary consent form. Emotional intelligence was assessed with a 60-item measurement tool developed by Bar-On and adapted into Turkish by Köksal. Students' attitudes were measured using the 24-item “Physical Education and Sports Attitude Scale” developed by Demirhan and Altay. The data were analyzed with SPSS 25 program. Normality tests revealed that the data were normally distributed, so independent sample t-test and one-way analysis of variance (ANOVA) were used. The significance level was set at 0.05. Analyses revealed significant differences in physical education and sport attitude scores and emotional intelligence scores based on gender and participation in sport activities. In addition, significant differences were observed in emotional intelligence scores depending on the educational level of the parents. However, no significant differences were found in physical education and sport attitude scores depending on these variables. The findings were discussed in the light of the literature and recommendations were made.